Advantages of Minimizing Energy Exchange Instead of Energy Cost in Prosumer Microgrids - Eva González-Romera; Mercedes Ruiz-Cortés; María-Isabel Milanés-Montero; Fermín Barrero-González; Enrique Romero-Cadaval; Rui Amaral Lopes; João Martins (Energies, 2019)
Microgrids of prosumers are a trendy approach within the smart grid concept, as a way to increase distributed renewable energy penetration within power systems in an efficient and sustainable way. Single prosumer individual management has been previously discussed in literature, usually based on economic profit optimization. In this paper, two novel approaches are proposed: firstly, a different objective function, relative to the mismatch between generated and demanded power, is tested and compared to classical objective function based on energy price, by means of a genetic algorithm method; secondly, this optimization procedure is applied to batteries’ coordinated scheduling of all the prosumers composing a community, instead of single one, which better matches the microgrid concept. These approaches are tested on a microgrid with two household prosumers, in the context of Spanish regulation for self-consumption. Results show noticeably better performance of mismatch objective function and coordinated schedule, in terms of self-consumption and self-sufficiency rates, power and energy interchanges with the main grid, battery degradation and even economic benefits.